1996
DOI: 10.1159/000126940
|View full text |Cite
|
Sign up to set email alerts
|

Differential Neuroendocrine and Behavioral Responses to Cocaine in Lewis and Fischer Rats

Abstract: Lewis (LEW) and Fischer 344 (F344) rats differ in responsiveness of the hypothalamo-pituitary-adrenocortical (HPA) axis as well as in their behavioral responses to drugs of abuse. The present experiments were conducted to compare hypothalamic corticotropin-releasing factor (CRF), plasma adrenocorti-cotropic hormone (ACTH) and plasma corticosterone (CS) responses to cocaine (0–60 mg/kg, i.p.) in LEW and F344 rats. Acute administration of cocaine resulted in decreases in CRF and dose-related increases in CS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
0
8
2
Order By: Relevance
“…Consistent with the results of the present study that utilized a circular locomotor apparatus, other studies using a different inescapable environment, the open field, report that F344 rats show greater exploratory behavior as assessed by inner versus outer area movement ratio (Glowa et al 1992b;Sternberg et al 1992). In contrast to the results of the present study, some researchers report greater activity levels in Lewis rats in a novel, inescapable apparatus (Camp et al 1994;Ambrosio et al 1995;Rex et al 1996;Paulus et al 1998) but others report no strain differences (Kosten et al 1994b;Simar et al 1996;Stohr et al 1998). Differences in type of measure, procedure or apparatus may underlie these discrepancies across studies.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Consistent with the results of the present study that utilized a circular locomotor apparatus, other studies using a different inescapable environment, the open field, report that F344 rats show greater exploratory behavior as assessed by inner versus outer area movement ratio (Glowa et al 1992b;Sternberg et al 1992). In contrast to the results of the present study, some researchers report greater activity levels in Lewis rats in a novel, inescapable apparatus (Camp et al 1994;Ambrosio et al 1995;Rex et al 1996;Paulus et al 1998) but others report no strain differences (Kosten et al 1994b;Simar et al 1996;Stohr et al 1998). Differences in type of measure, procedure or apparatus may underlie these discrepancies across studies.…”
Section: Discussioncontrasting
confidence: 76%
“…Compared to F344 rats, Lewis rats show greater conditioned place preference for drugs (Guitart et al 1992;Kosten et al 1994b;Horan et al 1997) and heightened acquisition of drug self-administration (Ambrosio et al 1995;Kosten et al 1997;Suzuki et al 1988). Yet, Lewis rats, compared to F344 rats, have blunted corticosterone levels both basally (Griffin and Whitacre 1991;Dhabhar et al 1993;Ortiz et al 1995) and in response to acute cocaine administration (Simar et al 1996) or acute stress (Sternberg et al 1992;Dhabhar et al 1993). In contrast to the fairly consistent findings of strain differences in these behavioral and hormonal measures, studies of locomotor activity levels in a novel environment report conflicting results (Camp et al 1994;Kosten et al 1994b;Ambrosio et al 1995;Rex et al 1996;Stohr et al 1998;Haile et al 2001b).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier reports on response to novelty in these rat strains have been somewhat inconsistent (Camp et al 1994;Rex et al 1996;Simar et al 1996;Stöhr et al 1998;Haile et al 2001;Miserendino et al 2003). Methodological differences, as well as established strain differences to stress, likely contributed to these conflicting results.…”
Section: Discussionmentioning
confidence: 97%
“…As an example, stress-or drug-induced corticosterone release is attenuated in Lewis compared to Fischer rats (Simar et al 1996). Cador et al suggested that rats with a high stress-induced corticosterone release show higher amphetamine-induced locomotion and are more likely to develop amphetamine self-administration (Cador et al 1993).…”
Section: Sensitivity and Sensitization To Systemic Amphetamine Challengementioning
confidence: 99%